230k views
0 votes
Please help asap
I cant figure out the answer

Please help asap I cant figure out the answer-example-1
User Gsakkis
by
4.7k points

1 Answer

12 votes

Answer:

3

Explanation:


x=√(2x+3)

square both sides:
x^2=2x+3

subtract
2x + 3 from both sides:
x^2-2x-3=0

factorize:
(x-3)(x+1)

Therefore,
x=3 \ and \ -1

Substitute found values of
x back into original equation:


3=√(2*3+3)=3 \ \ \checkmark


-1=√(2*-1+3)=1 incorrect!

So answer is
x = 3 only

User UbiQue
by
5.1k points